Strategic Formulation Towards A Prosperous Mosque : Case Study Of Izzatul Mu’minin Mosque Lembang - Mohamad Fadhian Budiman; Rina Djunita Pasaribu; Mohammad Riza Sutjipto; Dodie Tricahyono (Journal of Social Research, 2024)
The Izzatul Mu'minin Mosque (MIM) in Lembang is not solely focused on ritual worship activities but must also have a direct impact on the wider community. The prosperity of the mosque is achieved if MIM can become a center of civilization at the regional level through four aspects: worship, social, economic, education, and da'wah. This study aims to analyze the internal and external factors of MIM and formulate appropriate strategies to develop a prosperous mosque in accordance with the guidelines of the Ministry of Religious Affairs of the Republic of Indonesia and in line with the Quranic verse At-Taubah 18. A qualitative research method is used to deeply understand the mosque's context, focusing on solving actual problems that can be practically utilized. Data collection techniques include observation, interviews, and document studies. This study focuses on strategy formulation with a strategic management approach that is academically accountable and contributes to professional development as well as benefiting the wider community. Validation and credibility of the research are carried out through triangulation of methods and data sources with several informants involved in the mosque. Through the stages of the IE Matrix and SWOT Matrix, where the IE Matrix shows MIM's position in Cell 5 (Hold & Maintain), and SWOT produces strategic recommendations outlined in the QSPM for implementation. These strategies include: Increasing communication forums and making MIM a place for formal and informal deliberations; Collaborating with external communities for social activities; Digitizing the mosque with adequate technological infrastructure; Improving supporting facilities such as bathrooms and ablution places; Providing rest facilities for worshippers and tourists; Establishing a baitul mal or accountable financial body by conducting independent audits.